Connecting factories and related IT environments to manufacturing clouds. (2nd January 2015) - Rauschecker, Ursula; Stock, Daniel; Stöhr, Matthias; Verl, Alexander
Cloud manufacturing is an emerging concept related to the management of flexible production networks such as virtual enterprises. It not only suggests management approaches such as service-orientation in manufacturing but also provides solutions for efficient execution of the production network management by means of IT tools. Such tools are in most cases represented by cloud manufacturing platforms to which the managed production facilities are connected. However, when integrating factories and their IT infrastructure to cloud manufacturing environments, considerable effort is necessary to implement appropriate IT interfaces. In order to overcome this issue, this paper suggests a concept for a configurable interface component, i.e. factory adapter, which enables to easily configure and execute data exchange between factory-internal IT systems with manufacturing clouds. Especially small and medium-sized companies as well as enterprises participating in short-term or ad-hoc production networks will benefit from a factory adapter which helps to decrease efforts for IT interface implementation during supply chain integration.